Answer:
2x^2+7x+6
Explanation:
Expand the polynomial (An algebraic expression) using the FOIL (First, Outer, Inner, Last) method.
2x^2+7x+6
(x+2)(2x+3)
First, multiply the variables (x).
(x)(2x) = 2x^2
- NOTE: the '^' before a number is used to signify an exponent.
Then, multiply the whole numbers (2, 3).
(2)(3) = 6
Now, you're not done. You need to multiply the variables and the whole numbers (that weren't already multiplied together)
(x)(3) = 3x
(2)(2x) = 4x
- NOTE: make sure you're multiplying one expression to the other, not multiplying the same expression together.
Finally, add them all together, and simplify.
2x^2 + 6 +3x + 4x
=
2x^2+7x+6